Assessment of School Environmental Health Conditions in Governmental Primary Schools: A Cross-Sectional Study in El-Obeid City, North Kordofan State, Sudan - Mohammed, Musa Adam Osman Mohammed; Alim, Jibril Abdi Jimale; Koko, Eyman Ahmed Abdrahum (Al-Sihah : The Public Health Science Journal, 2025)
Ensuring environmental health in schools is vital for promoting student well-being and learning outcomes, particularly in under-resourced rural settings. However, evidence on environmental health conditions in Sudanese schools is limited. This study aimed to assess the school environmental health conditions in governmental primary schools in El-Obeid City, North Kordofan State, Sudan. Sixteen governmental basic schools were surveyed. A cluster random probability sampling technique was used to select schools. A structured checklist form was used for data collection. Data were managed and analyzed using descriptive statistics within a cross-sectional framework. Final results were presented and interpreted in tables.The results showed that 93% of schools were located at a suitable distance from public services, pollution, and noise. All school buildings were deemed acceptable. Fifty percent of schools had poor ventilation. Fifty percent of schools had access to reliable sources of clean and safe water. Latrines were available in 75% of schools. None of the schools had hand-washing facilities or soap for hand washing. Approximately 43.7% of schools burned solid waste directly. About 56.3% of schools had a canteen or cafeteria. There was a complete absence of hand-washing facilities in all schools and a lack of solid waste disposal services provided by local authorities. Urgent improvements are needed in sanitation and waste management.